Poly(norepinephrine)-coated FeOOH nanoparticles as carriers of artemisinin for cancer photothermal-chemical combination therapy. Issue 18 (29th March 2019) - He, Zi; Su, Huiling; Shen, Yuqing; Shi, Wei; Liu, Xin; Liu, Yang; Zhang, Fuhui; Zhang, Yansheng; Sun, Yanan; Ge, Dongtao
Abstract : Tumor-specific FeOOH@PNE-Art nanoparticles were fabricated that showed high efficacy of photothermal-chemical combination therapy and low toxicity to normal tissue. Abstract : The photothermal-chemical combination therapy is a promising approach for cancer treatment, however, chemotherapy often causes severe toxic and side effects on normal tissues. Herein, tumor-specific FeOOH@PNE-Art nanoparticles were fabricated via coating poly(norepinephrine) (PNE) on FeOOH nanoparticles, followed by loading of artemisinin (Art). The as-prepared nanoparticles exhibited excellent biocompatibility, strong near-infrared (NIR) absorbance and pH-responsive synchronous release of Art and iron ions. The released iron ions could not only supply iron ions in cancer cells which mediate endoperoxide bridge cleavage of Art and generate reactive oxygen species (ROS), but also react with H2 O2 at tumour sites via the Fenton reaction and produce hydroxyl radicals, inducing a tumour-specific killing. Moreover, owing to the synchronous release of Art and iron ions as well as the low leakage of iron ions, FeOOH@PNE-Art nanoparticles showed extremely low toxicity to normal tissue. Under NIR light irradiation, the tumours in FeOOH@PNE-Art injected mice were thoroughly eliminated after 7 days of treatment and no tumour recurrence was found 30 days after treatment, manifesting very high efficacy of combination therapy.